Sinergi Antara Kurikulum Merdeka dan Pendidikan Kebencanaan dalam Membangun Kesiapsiagaan di Satuan Pendidikan - Ficky Adi Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2025)
Indonesia is a country with a high level of disaster vulnerability due to its location at the meeting point of three world tectonic plates and the Pacific Ring of Fire region. The Merdeka Curriculum provides a strategic opportunity in integrating disaster education to equip students with understanding, skills, and responsive attitudes to disaster risks. Through a contextual and participatory approach, schools can become centers of preparedness that not only train students but also strengthen collective awareness in dealing with emergency situations. The purpose of this study is to analyze the synergistic relationship between the Merdeka Curriculum and disaster education to strengthen preparedness in educational units in Indonesia. The method used in this study is a literature study. The results of the study show that the Merdeka Curriculum opens great opportunities for strengthening disaster education through integration in various subjects and strengthening student character in accordance with the Pancasila Student Profile. Although there are still implementation challenges, such as limited teacher understanding and lack of national standards, holistic strategies, policy support, and cross-sector collaboration can encourage the realization of effective, sustainable, and contextual disaster education in educational units.